Hubungan Dialektikal Bahasa dan Praksis Sosial dengan Menggunakan Model Dialog dalam Syair Adat Sono Odi (Pemotongan Batu Kubur) Masyarakat Wewewa, Sumba Barat Daya: Kajian Ekolinguistik - Yuliana Sesi Bitu; Yohana Renda (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2021)
This study aims to determine the dialectical relationship of language and social praxis by using the Dialogue Model in the Sono Odi customary poetry (cutting of grave stones) of the Wewewa Community, Southwest Sumba. This research is included in the type of qualitative descriptive research. Methods and data collection techniques used in research is the method of listening to the basic techniques of tapping or recording. In its implementation, the basic technique of tapping is assisted by two advanced techniques, namely the free listening technique and the recording technique. The data analysis methods and techniques used in this study are the extralingual equivalent method with contextual techniques. The results of the data analysis show that the use of language in the traditional poetry of sono odi (cutting of grave stones) of the Wewewa community, Southwest Sumba has a close relationship with nature and socio-cultural relations between humans and humans, humans and nature, humans and ancestors, and humans and God. as its creator. These relationships can be seen using the dialogue method (Bang & Doors, 1993) by analyzing the meaning of a metaphor using ecolinguistic studies, namely the older generation as text makers (S1) and younger people as speech partners (S2) in a subject. or anonymous categories which are sociocultural constituents (S3). Giving advice and advice takes place within an ideological, sociological and biological TOPOS environment which refers to a condition (O) that exists in the Wewewa community, Southwest Sumba